A traffic aware, energy-efficient MAC protocol for Wireless Sensor Networks. (9th April 2009) - Gong, Haigang; Cao, Jiannong; Liu, Ming; Chen, Lijun; , Li Xie
In this paper, we propose TA-MAC, a traffic load adaptive, energy-efficient Medium Access Control (MAC) protocol for Wireless Sensor Networks (WSNs). TA-MAC modifies the contention window mechanism of S-MAC, a mostly well-known MAC scheme for sensor networks. Each sensor node chooses an optimal size of initial contention window according to the number of its neighbours. Then, it adjusts the initial contention window according to the current traffic load to reduce the collision probability while employing a fast back-off scheme to reduce the time for idle listening during back-off procedure, which both reduce the energy consumption. Simulation results show that TA-MAC outperforms S-MAC under high load.